Effective resistance to powdery mildew in Aegilops L. accessions - M. A. Kolesova; N. N. Chikida; M. Kh. Belousova; L. G. Tyryshkin (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Powdery mildew (Blumeria graminis (DC.) E.O. Speer f. sp. tritici Em. Marchal) is widespread and harmful in all regions of bread wheat cultivation. Severe development of powdery mildew leads to a decrease in the number and weight of grains. Growing resistant cultivars is the most environmentally friendly and economically profitable method to protect wheat from the disease. Development of such cultivars requires a search for new donors of effective genes controlling the resistance. To expand the genetic diversity of wheat for resistance to B. graminis, wild relatives of Triticum aestivum L., including Aegilops L. spp., are widely used. The aim of this work was to characterize seven Aegilops spp. for effective seedling and adult plant resistance to powdery mildew.Materials and methods. The material of the study consisted of 437 accessions representing 7 Aegilops spp. (Ae. speltoides Tausch, Ae. caudata L., Ae. biuncialis Vis., Ae. tauschii Coss., Ae. cylindrica Host, Ae. crassa Boiss. and Ae. ventricosa Tausch) from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR, St. Petersburg). Juvenile resistance was studied when the seedlings were inoculated with the agent of powdery mildew under controlled laboratory conditions; the adult plant resistance, after artificial inoculation of the plants and under natural infection in the fields of Pushkin and Pavlovsk Laboratories of VIR. Complex populations of the B. graminis agent were used for inoculation. The types of response to infection were scored 10 days after inoculation according to a conventional scale.Results and conclusions. As a result of the tests, susceptibility to powdery mildew was shown in all Aegilops accessions of the D-genome group; all the studied representatives of Ae. speltoides, Ae. caudata and Ae. biuncialis were highly resistant to powdery mildew.